2005
DOI: 10.1136/adc.2005.072264
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal predictors of chronic lung disease in very preterm infants

Abstract: Objective: To identify prenatal risk factors for chronic lung disease (CLD) at 36 weeks postmenstrual age in very preterm infants. Population: Data were collected prospectively as part of the ongoing audit of the Australian and New Zealand Neonatal Network (ANZNN) of all infants born at less than 32 weeks gestation admitted to all tertiary neonatal intensive care units in Australia and New Zealand. Methods: Prenatal factors up to 1 minute of age were examined in the subset of infants born at gestational ages 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
56
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 33 publications
(18 reference statements)
4
56
0
4
Order By: Relevance
“…These were not the expected results and could help explain the contradictory findings in the literature. Indeed, previous studies found a positive association 21,23,33 or no association 10,25,34 between placentamediated complications and BPD. However, a few studies distinguished between preeclamptic women with and without FGR.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These were not the expected results and could help explain the contradictory findings in the literature. Indeed, previous studies found a positive association 21,23,33 or no association 10,25,34 between placentamediated complications and BPD. However, a few studies distinguished between preeclamptic women with and without FGR.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found an association with BPD, [21][22][23] but others did not. 10,24,25 Most studies focused on maternal disorders but did not look at fetal consequences of placenta-mediated pregnancy complications.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…La mayor frecuencia de DBP en el sexo masculino sería otra señal que factores genéticos estarían involucrados en la patogenia de la DBP 11,51 . La forma por la cual el género masculino predispondría al desarrollo de DBP aún no esta claramente precisada.…”
Section: Factores Genéticosunclassified